ANALISIS KONSEP TENTANG WANITA AMINA WADUD - Baiq Tuhfatul Unsi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
Amina Wadud is a Muslim woman who is also a feminist. Her work on women in the Qur'an is set within a historical framework relating to the struggle of African-American women for gender equality. Amina Wadud's research aims to establish specific criteria to analyze the extent to which women's position in Muslim culture accurately reflects the meaning of Islam for women in life in society. Furthermore, the specific objective is to reveal the ability to adapt the worldview of the Qur'an to issues and the world of women according to the modern context. Amina Wadud uses the tauhid interpretation method in interpreting the Qur'an. The approach to reading tauhid as a hermeneutics in which each verse is evaluated in this study: 1) viewed from the context; 2) in the context of the discussion of the Qur'an on the same topic; 3) from the language as well as using the same grammatical structure used elsewhere in the Qur'an; 4) from the principles of the Qur'an which reject it; 5) from the context of the Weltanschauung of the Qur'an, or its world view. Amina Wadud argues,